2021
DOI: 10.3390/polym13172908
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Dielectric Properties of Rubber Materials

Abstract: According to specific formulas, the mixing of rubber samples occurs by two methods: open mixing and internal mixing. The effects of frequency, mixing process, carbon black (CB) content, zinc oxide (ZnO) content, and stearic acid (SA) content on the dielectric properties of rubber materials were studied. The results showed that the effects of the mixing process on the dielectric properties of the rubber samples cannot be ignored, and the appropriate mixing process should be selected when preparing the required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…LISWS samples may have a denser microstructure with fewer pores, which would allow for a stronger polarization. For all samples, there is a peak in dielectric constant around 450 °C, which could be attributed to subtle phase transition changing crystal structure or atom arrangement at elevated temperature [29]. Different samples, due to their slightly different microstructures, respond to the temperature differently.…”
Section: Resultsmentioning
confidence: 93%
“…LISWS samples may have a denser microstructure with fewer pores, which would allow for a stronger polarization. For all samples, there is a peak in dielectric constant around 450 °C, which could be attributed to subtle phase transition changing crystal structure or atom arrangement at elevated temperature [29]. Different samples, due to their slightly different microstructures, respond to the temperature differently.…”
Section: Resultsmentioning
confidence: 93%
“…However, a recent study conducted by Chen et al [42] revealed that even increasing the processing aids; accelerator (steric acid, SA) content actually caused a drop in the dielectric constant whilst increase in the activator zinc oxide (ZnO) and filler content both caused an increase in dielectric constant and the loss factor of NR. These imply that further work is required to address the issues of elastomer-GDNbased dielectric challenges especially with their processing techniques and material design.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium niobate (LiNbO 3 ) has been used for decades with optimal results [ 13 , 14 ]; however, it is characterised by low phase velocities that comport thinner piezoelectric layers and the fragility of the structures. In contrast, zinc oxide (ZnO) is a promising choice for thin-film resonators because its phase velocities cause the working frequency to be in the GHz range with layers that are a few micrometres thick at the cost of higher dielectric losses [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%